2015
DOI: 10.1631/jzus.b1400181
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin calcium improves endothelial function and delays the progress of atherosclerosis in patients with hypercholesterolemia

Abstract: Background: Statins have proven efficacy in inhibiting the onset and progress of atherosclerosis. The effectiveness of pitavastatin in reversing carotid atherosclerosis associated with hypercholesterolemia (HC) is unknown. Objectives: To explore the simultaneous effects of pitavastatin calcium on brachial arterial flow-mediated vasodilatation (FMD), carotid intima-media thickness (IMT), and arterial stiffness (β), three surrogate markers of atherosclerosis were studied in HC patients. Methods: A randomized, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Accordingly, Lactobacillus plantarum PCS26 has the potential to promote biliary cholesterol efflux and inhibit intestinal absorption, but it also warrants study in in vivo clinical trials for further assessment. Statins are extremely effective at reducing cardiovascular risk, as demonstrated in clinical studies that have confirmed the inhibition of the onset and progression of atherosclerosis (Zhao et al, 2015). Byun et al reported that pravastatin enhances hepatic bile acid synthesis via the PPARγ-LXRα-CYP7A1 pathway and activates PPARγ-LXRα-ABCG5/ABCG8, which excretes cholesterol into bile (Byun et al, 2014).…”
Section: ! 49mentioning
confidence: 99%
“…Accordingly, Lactobacillus plantarum PCS26 has the potential to promote biliary cholesterol efflux and inhibit intestinal absorption, but it also warrants study in in vivo clinical trials for further assessment. Statins are extremely effective at reducing cardiovascular risk, as demonstrated in clinical studies that have confirmed the inhibition of the onset and progression of atherosclerosis (Zhao et al, 2015). Byun et al reported that pravastatin enhances hepatic bile acid synthesis via the PPARγ-LXRα-CYP7A1 pathway and activates PPARγ-LXRα-ABCG5/ABCG8, which excretes cholesterol into bile (Byun et al, 2014).…”
Section: ! 49mentioning
confidence: 99%
“…The literature illuminates that exercise can improve vascular endothelial function in various ways, such as reducing blood lipids, blood glucose, and blood pressure levels, promoting nitric oxygen release, etc. [ 47 , 48 ]. Tanahash et al [ 49 ] conducted 12 weeks of aerobic training in 102 adults and found that the brachial artery WSS increased after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Esses estudos utilizaram técnicas de ultrassom não-invasivas, como a dilatação mediada por fluxo (DMF), que mede o fluxo mediado da artéria braquial, e a espessura médio-intimal da carótida (IMT, do inglês intima-medial thickening) e relataram resultados conflitantes. [9][10][11][12] Para contribuir com essa discussão, nosso estudo tem como objetivo avaliar os fatores associados à melhora da função endotelial e espessura da carótida medida por DMF e IMT em indivíduos com HIV, com carga viral sob controle, que foram tratados com uma combinação de atorvastatina + aspirina por um período de 6 meses.…”
Section: Introductionunclassified